Handbook of brief cognitive behaviour therapy - Bond, Frank W.; Dryden, Windy (Wiley, 2004)
Brief Cognitive Behaviour Therapy can be applied to the treatment of a wide range of problems in many different settings. In this unique handbook, Frank Bond and Windy Dryden, have brought together a prominent cast of authors, to discuss issues concerning the definition, assessment and, in particular, the practice of brief Cognitive Behaviour Therapy (CBT).